A Study on the Adoption of a Mobile Government Model for the Kingdom of Bahrain From the Perspective of the Government and Services Providers - Ahmed Hasan, Sowaileh (2011)
M-government is the utilization of mobile and wireless communication technology to enhance the delivery of e-government services. Due to the advanced status of e-government and the high mobile phone penetration, there is a great opportunity to utilize mobile technologies to improve the delivery of e-government services in Bahrain. This utilization is currently moving in a slow pace relatively to the utilization of traditional non-mobile technologies. Some of the small services are delivered through the mobile portal and can be accessed through the limited interface of mobile phones, however many of the more complex services that require large amounts of data and involve complex transactions are more difficult to deliver as mobile services. This research was an attempt to study M-government in order to develop a model to guide the adoption of m-government in Bahrain’s government organizations. It followed two research paths, one was to study the level of readiness of Bahrain’s government organizations to the adoption of m-government, and the other was to study the services provided by the government organizations in order to tackle their complexity and to develop a method to simplify their delivery as mobile services. The first path involved the distribution of a questionnaire to IT professionals involved in the development and support of e-government services. The second path involved the analysis of a sample of 40 government services. The main finding of the first path was the identification of important strengths that should be exploited and weaknesses that should be addressed to enhance the adoption of m-government by Bahrain’s government organizations. The main finding of the second path was the conclusion that an effective approach to utilize mobile technologies in a complex government service is to break the service into components and to identify the components that can be delivered through the mobile phone interface instead of attempting to deliver the whole service as a mobile service. The results of the two research paths were combined to build the target M-Government Adoption Model for Bahrain. That model outlined the important steps required to enable the adoption of M-government in Bahrain